Using UAV to detect shoreline changes: Case study - pohranov pond, Czech Republic - Čermáková Ivana; Komárková Jitka; Sedlák Pavel (International Society for Photogrammetry and Remote Sensing, 2016)
The paper describes utilization of an unmanned aerial vehicle (UAV) for detection of changes of shorelines. UAV is used as a cheep and on-demand available possibility how to collect remotely sensed data. Its utilization is limited by legal regulations and weather conditions. Paper deals with utilization of UAV for monitoring small water area and particularly study of changes of shorelines. Study contains other methods of classification. After classification will be data processed for next calculations. Indices regarding shoreline changes are in the study also. In conclusion, study contains obtainment findings and encouragement for the future.
Využití UAV pro detekci změn břehových linií: Případová studie - Pohránovský rybník, Česká republika
Keywords: Landscape; Pohranov pond; landscape indices; UAV; change the landscape; Krajina; Pohranovsky rybnik; krajinářské indexy; UAV; změny krajiny